Tavşan Adası, T ürkei: Die Arbeiten des Jahres 2012 - Bertemes, François (e-Forschungsberichte des DAI, 2023)
Tavşan Adası lies north of Panormos, the ancient harbour of Didyma, in western Turkey. It represents the head of a former headland that connected the island with the Turkish mainland 200 m afar. Since 2006, systematic excavations are carried out by the Martin-Luther-University Halle-Wittenberg. The main target of our fieldwork is to explore an important trading settlement from the first half of the 2nd millennium BC equipped with two natural harbours. Typical “Minoan” finds and complex architectural remains are deeply influenced by those in Crete and the Cyclades. Many imports from the southern and the eastern Aegean as well as their local imitations allow us to throw light upon the role of the Carian Coast within the Minoan communications network. In conjunction with the results from Miletus and Iasos we will thus be able to clarify its economic and cultural role in the 2nd millennium BC.